Cis-clerodane-type furanoditerpenoids from Tinospora crispa - Choudhary, Muhammad Iqbal; Muhammad Ismail,; Shaari, Khozirah; Ahmed Abbaskhan,; A. Sattar, Samina; Lajis, Md. Nordin; Atta-ur-Rahman, (American Chemical Society, 2010)
Phytochemical and cytotoxicity investigations on organic solvent extracts of the aerial parts of Tinospora crispa have led to the isolation of 15 cis-clerodane-type furanoditerpenoids. Of these, nine compounds (1-9) were found to be new. Spectroscopic assignments of a previously reported compound, borapetoside A (13), were revised on the basis of HMQC and HMBC correlations. No discernible activity was observed when compounds 10-13 were subjected to evaluation in cytotoxicity assays against human prostate cancer (PC-3) and the normal mouse fibroblast (3T3) cell lines.